WALI FILSUF: Konsep Wali dalam Tinjauan Tafsir Falsafi - Lukman Hakim Husnan (Al-Dirayah, 2019)
The idea of wali has a meaning that varies from one scientific discipline to another. What is meant in the terminology of the fuqoha (disciplines of jurisprudence) is clearly not the same as the description understood by the Sufis (disciplines of Sufism). This article is intended to trace the use of the term wali in the perspective of Muslim Philosophers (disciplines of philosophy)